Early malignant progression of hereditary medullary thyroid cancer - Machens, Andreas; Niccoli-Sire, Patricia; Hoegel, Josef; Frank-Raue, Karin; Vroonhoven, Theo J. van; Roeher, Hans-Dietrich; Wahl, Robert A.; Lamesch, Peter; Raue, Friedhelm; Conte-Devolx, Bernard; Dralle, Henning (The New England journal of medicine, 2003)
Germ-line mutations in the rearranged during transfection (RET) proto-oncogene are associated with thyroid cancer. These investigators studied presymptomatic patients 20 years of age or younger who had known RET mutations and had undergone prophylactic thyroidectomy. A significant age-related progression from C-cell hyperplasia to medullary thyroid carcinoma and to nodal metastasis was found in subgroups with certain mutations. Guidelines for the timing of thyroidectomy. Point mutations in the rearranged during transfection (RET) proto-oncogene1 have emerged as the molecular basis of an array of distinct clinical phenotypes2,3 as diverse as Hirschsprung's disease (aganglionosis of the submucosal and myenteric plexus of the colon), familial medullary thyroid carcinoma, and multiple endocrine neoplasia (MEN) type 2A (MEN-2A, characterized by medullary thyroid carcinoma, pheochromocytoma, and parathyroid adenoma) and type 2B (MEN-2B, characterized by medullary thyroid carcinoma, pheochromocytoma, intestinal ganglioneuromatosis, and skeletal deformity).4 Encoding a receptor tyrosine kinase on chromosome 10q11.2, RET germ-line mutations in humans affect essentially four types of tissue, all of which originate from . . .